Multiprotocol Communication Interface PMSM Control on Account of Industrial Configuration Software - Li-guo Zhang; Man-feng Dou (Journal of Electrical and Computer Engineering)
The purpose is to achieve drive controller of PMSM connect with industrial control configuration software seamless and to meet the industrial configuration software in the demand for motor to realize intelligent control. A software interface was designed and implemented about motor drive controller and the PC the industrial control configuration base on Modbus_RTU serial communication protocol of industrial control. One kind of design and implementation methods have been proposed in the communication interfaces for industrial applications scalable multiselectivity. Using the latest high-performance multiprotocol transceiver device pin programmable SP339 as the lower machine communications chip designed optional multi-interface hardware circuit with DSP TMS320F2812 as the processor. The interface program was studied with regard to C language software of lower machine and control configuration software of PC. Database creation, data acquisition, and animation links of PC configuration software are realized. Online debugging results meet the design requirements on account of PC control configuration software and the lower machine controller hardware and software.